AFRICAN HYMNODY IN CHRISTIAN WORSHIP: A CONTRIBUTION TO THE HISTORY OF ITS DEVELOPMENT by A.M. Jones, Mambo Press, Gwelo, Rhodesia, 1976 (Mambo Occasional Papers — Misso-Pastoral Series No. 8), pp. 64, RS0.65. - Kaemmer, John E. (International Library of African Music, 1980)
pages: 129-130
Keywords: African Music; African Hymnody; Christian Worship